The control of small medium banks profitability using financial modeling approach under certainty and uncertainty - Konstantinos J. Liapis; Sotirios J. Trigkas (Financial Studies, 2019)
Following a prototype economic modellingapproach for Small-Medium Banks (SMBs) business plans according to structure of Additional Funds Needed (AFN) models this paper examines the volatility of banking efficiency in terms of Key Profitability Variables (KPVs) in order to determine Key Performance Indicators (KPIs). The KPVs are the size and structure of deposits, loans and their interest rates. Initially we examine the intervals in which the KPVs of the SMBs are moving. Then we conduct a sensitivity analysis under certainty. Our paper providesfirst evidence that business plans following AFN economic models are worthy tools for financial planning of SMBs in order to control their performance, contributing to budgeting and decision making for SMBs strategic planning. Financial planning of SMBs in order to control their performance, contributing to budgeting and decision making for SMBs strategic planning, prove to be a critical process for the overall bank efficiency. With this paper we contribute to debate regarding the introduction economic modellingapproaches under certainty and uncertainty in the banking industry.
Keywords: G21; M41; C44; 330; Bank performance; AFN models; Operation Research